Effect of supplementing low–protein diets with essential amino acids on growth performance of broiler chickens under the hot and humid tropical conditions - Awad Mohamed, Elmutaz Atta; Razali, M. R. M.; Idrus, Zulkifli; Soleimani Farjam, Abdoreza; Loh, Teck Chwen (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A three weeks trial was conducted to determine the effect of lowering crude protein (CP) with optimal amino acid (AA) profile on performance of broilers under tropical hot and humid environment. Five isocaloric (3023 ME/kg) experimental diets in which the CP was gradually reduced by 1.5% from 22.2% to 16.2% were formulated to meet or exceed NRC (NRC, 1994) recommendations from 1-21d except for the protein and metabolizable energy. Body weight (BW) and weight gain (WG) were significantly (P≤ 0.001) decreased, feed intake (FI) significantly (P≤0.05) decreased, whereas, feed conversion ratio (FCR) was significantly (P≤ 0.0003) increased when CP reduced.